LAND MANAGEMENT AND ECONOMIC IMPROVEMENT OF PALA PLANTATIONS IN THE BANDA ISLAND AFTER COLONIALIZATION 1954-2018 - Djumadi Djunaidy (Erudio Journal of Educational Innovation, 2022)
In the 14th and 15th centuries, European countries desperately needed the spice nutmeg, which was used for a variety of purposes, such as preserving fresh meat in cattle, for medical and dietary purposes, and in claims about its health and virility properties. The high demand for the commodity nutmeg opened up trade networks that stretched from Asia to Africa and Europe. Banda Naira, as a nutmeg-endemic region, has been connected for centuries. This study uses a qualitative method with a socio-historical perspective and aims to analyze the Banda nutmeg spice management model from 1945 to 2018. The research findings show that the distribution pattern of post-colonization nutmeg plantations from 1945 to 2018 was carried out by lottery, which was specifically intended for people who had families based on their necessities of life. While the management pattern of nutmeg plantations includes the harvesting of nutmeg up to the drying of nutmeg, this is carried out by smoking and drying under the hot sun in order to produce quality dried nutmeg. This nutmeg spice management model has had a huge impact on the people of the Banda Islands, both positive and negative. The positive impact is bringing prosperity to the people of the Banda Islands, but the negative impact is land grabbing, theft, and manipulation of the quality of nutmeg.